PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSET DAN TOTAL ASSET TURNOVER TERHADAP PRICE TO BOOK VALUE PADA PERUSAHAAN SUBSEKTOR TELEKOMUNIKASI - Gita Dwi Nurita; Kartika Berliani (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to determine the effect DER, ROA, and TATO on PBV among companies in the telecommunication subsector. Applying a quantitative approach using secondary data in the form of financial statements of telecommunication subsector issuers on IDX for the 2019-2024 period. The results indicate that Only DER and ROA have a positive and significant effect on PBV, while TATO does not show a significant influence. This finding provides a theoretical contribution by serving as an academic reference for expanding knowledge on the factors that drive PBV. The result may also be used as a learning resource in relevant fields.In terms of practical contribution, the results provide empirical guidance  for investors, managers, and analysts in the telecommunication subsector in prioritizing the analysis of DER and ROA as key determinants of stock value. Keywords: Return On Asset, Telecommunication Industry, Total Asset Turnover, Price To Book Value, Debt To Equity Ratio